Electrochromic device and preparation method thereof

By chemical strengthening treatment of potassium ion of soda-lime glass substrate of electrochromic devices, the negative impact of sodium ion migration on film performance is solved, the device life is improved and the production cost is reduced.

CN119828387APending Publication Date: 2025-04-15ZHEJIANG JINGSHENG FILM TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510243201.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In existing electrochromic devices, sodium ion migration has a negative impact on the performance of the electrochromic film layer, causing the film layer to age and fall off, affecting the stability and service life of the device.

Method used

Sodalis glass treated with potassium ion chemical reinforcement is used as the substrate to replace sodium ions by potassium ions to form a more stable glass surface, thereby preventing the migration of sodium ions.

Benefits of technology

It effectively solves the impact of sodium ion migration on the electrochromic film layer, improves the service life of electrochromic devices, simplifies the production process and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119828387A_ABST
    Figure CN119828387A_ABST
Patent Text Reader

Abstract

The invention provides an electrochromic device and a preparation method thereof. A film layer structure of the electrochromic device sequentially comprises a glass substrate and an electrochromic film layer, the glass substrate is potassium ion chemical reinforced soda-lime glass; the film layer structure of the electrochromic film layer sequentially comprises a first transparent conductive layer, a cathode electrochromic layer, a lithium medium layer, an ion conduction layer, an anode electrochromic layer and a second transparent conductive layer from the direction of the glass substrate. According to the electrochromic device provided by the invention, through the substrate glass subjected to chemical toughening treatment by potassium ions, the influence of sodium ion precipitation of an existing electrochromic device on the electrochromic film layer is fundamentally solved, and the service life of the electrochromic device is prolonged; meanwhile, compared with a method of arranging a barrier layer between the substrate glass and the electrochromic film layer in the prior art, a coating process does not need to be added, the production process is simpler, and the cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochromic technology, and specifically relates to an electrochromic device and a preparation method thereof. Background Art

[0002] With the continuous development of electrochromic technology, its application in smart glass, automobiles, construction and other fields is becoming more and more extensive. The performance requirements of electrochromic products are getting higher and higher, especially the service life and film stability of the products. In these electrochromic products, the choice of substrate material and its combination with the color-changing film layer directly affect the long-term stability and service life of the product.

[0003] At present, the industry generally uses soda-lime-alkali glass or tempered soda-lime-alkali glass as electrochromic substrate. This type of glass contains more sodium ions, which are easy to cause sodium ion migration in the electrochromic film during high temperature treatment and subsequent voltage and use conditions. The migration of sodium ions will have a negative impact on the performance of the electrochromic film, causing aging, shedding or other adverse effects of the film, thereby affecting the stability of the film and reducing the service life of the product.

[0004] In order to deal with this problem, the current industry often uses a barrier layer between the glass and the color-changing film layer, such as niobium oxide, silicon oxide, silicon nitride, fluorine-doped tin oxide and other materials. For example, CN112020670A discloses an electrochromic device with color reflection and transmission, which includes a substrate, a diffusion barrier layer and a stack of staggered index matching layers in sequence, wherein the diffusion barrier layer is a silicon oxide layer. These barrier layers can reduce the migration of sodium ions to a certain extent, and their effect is limited to reducing the migration amount of sodium ions, but they cannot completely isolate the influence of sodium ions, and cannot fundamentally solve the problem of sodium ion precipitation. Moreover, this method requires adding additional coating steps and equipment to the production process, resulting in an increase in production costs.

[0005] Therefore, how to improve the stability of the substrate through more effective means and completely solve the impact of sodium ion migration on the electrochromic film layer without increasing additional production costs has become a technical problem that needs to be urgently solved in the current industry. Summary of the invention

[0006] The purpose of the present invention is to provide an electrochromic device and a preparation method thereof, and to solve the problem that sodium ions in soda-lime glass migrate and precipitate into the electrochromic film layer and affect the device performance by strengthening the glass substrate in the electrochromic device.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides an electrochromic device, wherein the film layer structure of the electrochromic device comprises: a glass substrate and an electrochromic thin film layer;

[0009] The glass substrate is potassium ion chemically strengthened soda lime glass;

[0010] The film structure of the electrochromic thin film layer includes, in order from the direction of the glass substrate, a first transparent conductive layer, a cathode electrochromic layer, a lithium dielectric layer, an ion conductive layer, an anode electrochromic layer and a second transparent conductive layer.

[0011] The electrochromic device provided by the present invention optimizes the film structure of the existing electrochromic device, uses a substrate glass that has been chemically tempered with potassium ions. During the tempering process using potassium ions, the potassium ions will replace the sodium ions on the surface of the glass. The diameter of the potassium ions is larger than that of the sodium ions, and the arrangement of the potassium ions on the surface of the glass is denser than that of the sodium ions, thereby locking the sodium ions in the glass and preventing them from migrating and precipitating, thereby fundamentally solving the influence of the sodium ion precipitation of the existing electrochromic device on the electrochromic film layer, and improving the life of the electrochromic device; at the same time, compared with the method of setting a barrier layer between the substrate glass and the electrochromic film layer in the prior art, there is no need to increase the coating process, the production process is simpler, and the cost is reduced.

[0012] In the present invention, the composition of the soda-lime glass includes: SiO2 70-75wt%, Na2O 5-20wt%, CaO 5-15wt%, K2O 1.5-6wt%, Al2O3 1-3wt%, and MgO 1-6wt%.

[0013] In the soda-lime glass, the content of K2O is 1.5-6wt%, for example, it can be 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt% or 6wt%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0014] Preferably, the potassium content in the potassium ion chemically strengthened soda-lime glass is 7-14wt%, for example, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt% or 14wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] Preferably, the first transparent conductive layer comprises ITO conductive glass.

[0016] Preferably, the thickness of the first transparent conductive layer is 300-800 nm, for example, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm or 800 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0017] Preferably, the cathode electrochromic layer comprises WO x .

[0018] Preferably, the thickness of the cathode electrochromic layer is 200-500 nm, for example, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm or 500 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0019] Preferably, the thickness of the lithium dielectric layer is 50-100 nm, for example, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0020] Preferably, the ion conducting layer comprises SiO2.

[0021] Preferably, the thickness of the ion conducting layer is 15-50 nm, for example, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0022] Preferably, the anode electrochromic layer comprises NiWO x .

[0023] Preferably, the thickness of the anode electrochromic layer is 200-500 nm, for example, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm or 500 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0024] Preferably, the second transparent conductive layer comprises ITO conductive glass.

[0025] Preferably, the thickness of the second transparent conductive layer is 300-800 nm, for example, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm or 800 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0026] Preferably, the thickness of the glass substrate is 0.4-5 mm, for example, 0.4 mm, 1.0 mm, 1.5 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm or 5 mm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0027] In a second aspect, the present invention provides a method for preparing the electrochromic device according to the first aspect, the preparation method comprising the following steps:

[0028] (1) placing soda-lime glass in a potassium salt solution for chemical tempering treatment to obtain potassium ion chemically strengthened soda-lime glass;

[0029] (2) Electrochromic thin film layers are sequentially deposited on the potassium ion chemically strengthened soda-lime glass by physical vapor deposition to obtain the electrochromic device.

[0030] Preferably, the temperature of the chemical tempering treatment is 400-450°C, for example, it can be 400°C, 405°C, 410°C, 415°C, 420°C, 425°C, 430°C, 435°C, 440°C, 445°C or 450°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, the chemical toughening treatment time is 4-6 hours, for example, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0032] Preferably, the potassium salt comprises potassium nitrate and / or potassium chloride.

[0033] Preferably, the concentration of the potassium salt solution is 99-100%, for example, it can be 99%, 99.1%, 99.2%, 99.3%, 99.4%, 99.5%, 99.6%, 99.7%, 99.8%, 99.9% or 100%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] The electrochromic device provided by the present invention fundamentally solves the influence of sodium ion precipitation on the electrochromic film layer of the existing electrochromic device by using the substrate glass chemically tempered with potassium ions, thereby improving the life of the electrochromic device; at the same time, compared with the method of setting a barrier layer between the substrate glass and the electrochromic film layer in the prior art, there is no need to add a coating process, the production process is simpler, and the cost is reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The film structure of the electrochromic device provided in Example 1;

[0037] Wherein: 1, glass substrate; 21, first transparent conductive layer; 22, cathode electrochromic layer; 23, lithium dielectric layer; 24, ion conduction layer; 25, anode electrochromic layer; 26, second transparent conductive layer;

[0038] Figure 2 is a TEM scan of the electrochromic device provided in Example 1;

[0039] Figure 3 is a TEM scan of the electrochromic device provided in Comparative Example 1;

[0040] Figure 4 The film structure of the electrochromic device provided in Comparative Example 2;

[0041] Wherein: 1, glass substrate; 3, barrier layer; 21, first transparent conductive layer; 22, cathode electrochromic layer; 23, lithium dielectric layer; 24, ion conduction layer; 25, anode electrochromic layer; 26, second transparent conductive layer;

[0042] Figure 5 This is a TEM scan of the electrochromic device provided in Comparative Example 2. DETAILED DESCRIPTION

[0043] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0044] In order to clearly illustrate the technical solution of the present invention, in a specific implementation manner, the composition of the soda-lime glass used includes: SiO2 72wt%, Na2O 11wt%, CaO 9wt%, K2O 5wt%, Al2O3 1.5wt%, and MgO 1.5wt%.

[0045] Example 1

[0046] This embodiment provides a Figure 1 The electrochromic device shown, the film structure of the electrochromic device includes:

[0047] Glass substrate 1 and electrochromic thin film layer.

[0048] The electrochromic thin film layer includes, in order from the direction of the glass substrate, a first transparent conductive layer 21 , a cathode electrochromic layer 22 , a lithium dielectric layer 23 , an ion conductive layer 24 , an anode electrochromic layer 25 and a second transparent conductive layer 26 .

[0049] The glass substrate 1 is potassium ion chemically strengthened soda lime glass with a thickness of 3 mm.

[0050] The first transparent conductive layer 21 is ITO conductive glass with a thickness of 500 nm.

[0051] The cathode electrochromic layer 22 is WO x , with a thickness of 300nm.

[0052] The thickness of the lithium dielectric layer 23 is 80 nm.

[0053] The ion conducting layer 24 is SiO2 and has a thickness of 30 nm.

[0054] The anode electrochromic layer 25 is NiWO x , with a thickness of 300nm.

[0055] The second transparent conductive layer 26 is ITO conductive glass and has a thickness of 500 nm.

[0056] The preparation method of the electrochromic device comprises:

[0057] (1) placing soda-lime glass in a potassium nitrate solution for chemical tempering treatment, wherein the concentration of the potassium nitrate solution is 99.5%, the temperature of the chemical tempering treatment is 420° C., the time of the chemical tempering treatment is 5 hours, and after the chemical tempering treatment, the glass is taken out and cooled to room temperature to obtain the potassium ion chemically strengthened soda-lime glass;

[0058] (2) A first transparent conductive layer, a cathode electrochromic layer, a lithium dielectric layer, an ion conducting layer, an anode electrochromic layer and a second transparent conductive layer are sequentially deposited on the potassium ion chemically strengthened soda-lime glass by a physical vapor deposition method to obtain the electrochromic device.

[0059] In this embodiment, the electrochromic device was scanned and analyzed using TEM to observe the microscopic state of sodium ion migration and precipitation. The results are as follows: Figure 2 As shown, sodium ions are shown in pink, and it can be seen that no sodium ions precipitate or migrate.

[0060] Example 2

[0061] This embodiment provides an electrochromic device, wherein the film structure of the electrochromic device includes:

[0062] Glass substrate and electrochromic thin film layer.

[0063] The electrochromic thin film layer includes, in order from the direction of the glass substrate, a first transparent conductive layer, a cathode electrochromic layer, a lithium dielectric layer, an ion conductive layer, an anode electrochromic layer, and a second transparent conductive layer.

[0064] The glass substrate 1 is potassium ion chemically strengthened soda lime glass with a thickness of 2 mm.

[0065] The first transparent conductive layer 21 is ITO conductive glass with a thickness of 300 nm.

[0066] The cathode electrochromic layer 22 is WO x , with a thickness of 500nm.

[0067] The thickness of the lithium dielectric layer 23 is 50 nm.

[0068] The ion conducting layer 24 is SiO2 and has a thickness of 50 nm.

[0069] The anode electrochromic layer 25 is NiWO x , with a thickness of 500nm.

[0070] The second transparent conductive layer 26 is ITO conductive glass and has a thickness of 800 nm.

[0071] The preparation method of the electrochromic device comprises:

[0072] (1) placing soda-lime glass in a potassium nitrate solution for chemical tempering treatment, wherein the concentration of the potassium nitrate solution is 100%, the temperature of the chemical tempering treatment is 400° C., the time of the chemical tempering treatment is 6 hours, and after the chemical tempering treatment, the glass is taken out and cooled to room temperature to obtain the potassium ion chemically strengthened soda-lime glass;

[0073] (2) A first transparent conductive layer, a cathode electrochromic layer, a lithium dielectric layer, an ion conducting layer, an anode electrochromic layer and a second transparent conductive layer are sequentially deposited on the potassium ion chemically strengthened soda-lime glass by a physical vapor deposition method to obtain the electrochromic device.

[0074] In this embodiment, the electrochromic device was scanned and analyzed using TEM to observe the microscopic state of sodium ion migration and precipitation. The result was the same as that in Embodiment 1, and no sodium ion precipitation and migration occurred.

[0075] Example 3

[0076] This embodiment provides an electrochromic device, wherein the film structure of the electrochromic device includes:

[0077] Glass substrate and electrochromic thin film layer.

[0078] The electrochromic thin film layer includes, in order from the direction of the glass substrate, a first transparent conductive layer, a cathode electrochromic layer, a lithium dielectric layer, an ion conductive layer, an anode electrochromic layer, and a second transparent conductive layer.

[0079] The glass substrate 1 is potassium ion chemically strengthened soda lime glass with a thickness of 4 mm.

[0080] The first transparent conductive layer 21 is ITO conductive glass with a thickness of 800 nm.

[0081] The cathode electrochromic layer 22 is WO x , with a thickness of 200nm.

[0082] The thickness of the lithium dielectric layer 23 is 100 nm.

[0083] The ion conducting layer 24 is SiO2 and has a thickness of 15 nm.

[0084] The anode electrochromic layer 25 is NiWO x , with a thickness of 200nm.

[0085] The second transparent conductive layer 26 is ITO conductive glass and has a thickness of 300 nm.

[0086] The preparation method of the electrochromic device comprises:

[0087] (1) placing soda-lime glass in a potassium nitrate solution for chemical tempering treatment, wherein the concentration of the potassium nitrate solution is 99%, the temperature of the chemical tempering treatment is 450° C., the time of the chemical tempering treatment is 4 hours, and after the chemical tempering treatment, the glass is taken out and cooled to room temperature to obtain the potassium ion chemically strengthened soda-lime glass;

[0088] (2) A first transparent conductive layer, a cathode electrochromic layer, a lithium dielectric layer, an ion conducting layer, an anode electrochromic layer and a second transparent conductive layer are sequentially deposited on the potassium ion chemically strengthened soda-lime glass by a physical vapor deposition method to obtain the electrochromic device.

[0089] In this embodiment, the electrochromic device was scanned and analyzed using TEM to observe the microscopic state of sodium ion migration and precipitation. The result was the same as that in Embodiment 1, and no sodium ion precipitation and migration occurred.

[0090] Example 4

[0091] This embodiment provides an electrochromic device, and the structure of the electrochromic device is the same as that of Embodiment 1.

[0092] Compared with Example 1, the method for preparing the electrochromic device is the same as Example 1, in which the temperature of the chemical tempering treatment in step (1) is controlled to be 350° C.

[0093] In this embodiment, the temperature of the chemical tempering treatment is insufficient, resulting in insufficient melting of potassium nitrate, a decrease in the chemical strengthening effect, and a decrease in the replacement effect of potassium ions. Compared with Example 1, sodium ions have slight precipitation and migration.

[0094] Example 5

[0095] This embodiment provides an electrochromic device, and the structure of the electrochromic device is the same as that of Embodiment 1.

[0096] Compared with Example 1, the method for preparing the electrochromic device is the same as Example 1, in which the temperature of the chemical tempering treatment in step (1) is controlled to be 500° C.

[0097] In this embodiment, the temperature of the chemical tempering treatment is too high, and the sodium ion migration and precipitation effect is not further improved. However, the high temperature will cause the stress on the glass surface to be too high and unevenly distributed, resulting in warping and affecting the process stability of subsequent product processes.

[0098] Comparative Example 1

[0099] This comparative example provides an electrochromic device, wherein the film structure of the electrochromic device comprises:

[0100] Glass substrate and electrochromic thin film layer.

[0101] The electrochromic thin film layer includes, in order from the direction of the glass substrate, a first transparent conductive layer, a cathode electrochromic layer, a lithium dielectric layer, an ion conductive layer, an anode electrochromic layer, and a second transparent conductive layer.

[0102] The glass substrate is soda-lime glass with a thickness of 3 mm.

[0103] The first transparent conductive layer is ITO conductive glass with a thickness of 500 nm.

[0104] The cathode electrochromic layer is WO x , with a thickness of 300nm.

[0105] The thickness of the lithium dielectric layer is 80 nm.

[0106] The ion conducting layer is SiO2 and has a thickness of 30 nm.

[0107] The anode electrochromic layer is NiWO x , with a thickness of 300nm.

[0108] The second transparent conductive layer is ITO conductive glass with a thickness of 500 nm.

[0109] That is, compared with Example 1, the potassium ion chemically strengthened soda-lime glass of the glass substrate is replaced with soda-lime glass, and the rest is the same as Example 1.

[0110] The preparation method of the electrochromic device comprises:

[0111] The electrochromic device is obtained by sequentially depositing a first transparent conductive layer, a cathode electrochromic layer, a lithium dielectric layer, an ion conduction layer, an anode electrochromic layer and a second transparent conductive layer on soda-lime glass by a physical vapor deposition method.

[0112] In this comparative example, the electrochromic device was scanned and analyzed using TEM to observe the microscopic state of sodium ion migration and precipitation. The results are as follows: Figure 3 As shown, sodium ions are shown in pink, and it can be seen that there is serious sodium ion migration and precipitation in the device.

[0113] Comparative Example 2

[0114] This comparative example provides a Figure 4 The electrochromic device shown, the film layer structure of the electrochromic device comprises in sequence:

[0115] Glass substrate 1, barrier layer 3 and electrochromic thin film layer.

[0116] The electrochromic thin film layer includes, in order from the direction of the glass substrate, a first transparent conductive layer 21 , a cathode electrochromic layer 22 , a lithium dielectric layer 23 , an ion conductive layer 24 , an anode electrochromic layer 25 and a second transparent conductive layer 26 .

[0117] The glass substrate 1 is soda-lime glass with a thickness of 3 mm.

[0118] The barrier layer 3 is SiO2 and has a thickness of 100 nm.

[0119] The first transparent conductive layer 21 is ITO conductive glass with a thickness of 500 nm.

[0120] The cathode electrochromic layer 22 is WO x , with a thickness of 300nm.

[0121] The thickness of the lithium dielectric layer 23 is 80 nm.

[0122] The ion conducting layer 24 is SiO2 and has a thickness of 30 nm.

[0123] The anode electrochromic layer 25 is NiWO x , with a thickness of 300nm.

[0124] The second transparent conductive layer 26 is ITO conductive glass and has a thickness of 500 nm.

[0125] That is, compared with Example 1, NbO is provided between the glass substrate and the electrochromic thin film layer. x The barrier layer and the rest are the same as those in Example 1.

[0126] The preparation method of the electrochromic device comprises:

[0127] The electrochromic device is obtained by sequentially depositing a SiO2 barrier layer, a first transparent conductive layer, a cathode electrochromic layer, a lithium dielectric layer, an ion conduction layer, an anode electrochromic layer and a second transparent conductive layer on soda-lime glass using a physical vapor deposition method.

[0128] In this comparative example, the electrochromic device was scanned and analyzed using TEM to observe the microscopic state of sodium ion migration and precipitation. The results are as follows: Figure 5 As shown, sodium ions are shown in pink. It can be seen that there is a certain amount of migration and precipitation of sodium ions. Although this is an improvement compared to Comparative Example 1, the problem of sodium ion migration and precipitation cannot be completely solved.

[0129] In summary, the electrochromic device provided by the present invention fundamentally solves the influence of sodium ion precipitation on the electrochromic film layer of the existing electrochromic device by chemically tempering the substrate glass with potassium ions, thereby improving the life of the electrochromic device; at the same time, compared with the method of setting a barrier layer between the substrate glass and the electrochromic film layer in the prior art, there is no need to increase the coating process, the production process is simpler, and the cost is reduced.

[0130] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. An electrochromic device, characterized in that: The film layer structure of the electrochromic device comprises in sequence: a glass substrate and an electrochromic thin film layer; The glass substrate is potassium ion chemically strengthened soda lime glass; The film structure of the electrochromic thin film layer includes, in order from the direction of the glass substrate, a first transparent conductive layer, a cathode electrochromic layer, a lithium dielectric layer, an ion conductive layer, an anode electrochromic layer and a second transparent conductive layer.

2. The electrochromic device according to claim 1, characterized in that: The potassium content of the potassium ion chemically strengthened soda-lime glass is 7-14 wt %.

3. The electrochromic device according to claim 1 or 2, characterized in that: The first transparent conductive layer comprises ITO conductive glass; Preferably, the thickness of the first transparent conductive layer is 300-800 nm; Preferably, the cathode electrochromic layer comprises WO x ; Preferably, the cathode electrochromic layer has a thickness of 200-500 nm.

4. The electrochromic device according to any one of claims 1 to 3, characterized in that: The thickness of the lithium dielectric layer is 50-100 nm; Preferably, the ion conducting layer comprises SiO2; Preferably, the ion conducting layer has a thickness of 15-50 nm.

5. The electrochromic device according to any one of claims 1 to 4, characterized in that: The anode electrochromic layer includes NiWO x ; Preferably, the thickness of the anode electrochromic layer is 200-500 nm.

6. The electrochromic device according to any one of claims 1 to 5, characterized in that: The second transparent conductive layer includes ITO conductive glass; Preferably, the thickness of the second transparent conductive layer is 300-800 nm; Preferably, the glass substrate has a thickness of 0.4-5 mm.

7. A method for preparing an electrochromic device according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) placing soda-lime glass in a potassium salt solution for chemical tempering treatment to obtain potassium ion chemically strengthened soda-lime glass; (2) Electrochromic thin film layers are sequentially deposited on the potassium ion chemically strengthened soda-lime glass by physical vapor deposition to obtain the electrochromic device.

8. The preparation method according to claim 7, characterized in that: The temperature of the chemical tempering treatment is 400-450°C.

9. The preparation method according to claim 7 or 8, characterized in that: The chemical toughening treatment time is 4-6 hours.

10. The preparation method according to any one of claims 7 to 9, characterized in that: The potassium salt includes potassium nitrate and / or potassium chloride; Preferably, the concentration of the potassium salt solution is 99-100%.

Citation Information

Patent Citations

  • Electrochromic device having color reflectance and transmission

    CN112020670A